Kontribusi Pendidikan Kewarganegaraan dalam Menangkal Radikalisme - Ridwan Ardi (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Radicalism is one of the major challenges in modern society, including in the educational environment. Citizenship Education (PKn) has a strategic role in countering radicalism by instilling the values ​​of democracy, tolerance, and nationalism in students. This literature study aims to analyze the contribution of PKn in shaping national attitudes and strengthening resilience to radicalism. This study was conducted through an analysis of various previous studies that discussed the relationship between PKn and deradicalization efforts. The results of the study indicate that effective PKn learning can improve students' understanding of national values, strengthen critical attitudes towards radical propaganda, and shape characters based on the spirit of diversity. Therefore, it is important for educational institutions to strengthen the PKn curriculum to prevent the spread of radicalism among the younger generation.